The Urgency of Objective Score Processing: A Qualitative Study on The Understanding of Scalling System, Score Distribution, and Assessment Standards in Educational Evaluation - Anisa Meilawati; Muh. Nur Rochim Maksum; Ari Anshori; Hana Ayu Safitri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Objective and transparent grading remains a critical challenge within educational evaluation system, particularly in contexts where inconsistency, subjectivitiy, and unclear assessment standards affect students' motivation and academic fairness. This study explores the urgency of objective score processing in education by examining teachers’ understanding and practices related to scale selection, score distribution, and standardized assessment criteria. Using a qualitative research design, data were collected through in depth interviews, observations, and documentation analysis in several senior high schools. Thematic analysis was employed to identify patterns in how educators interpret and implement objective grading principles. Findings indicate that while teachers recognize the importance of objective evaluation, variations in understanding of measurement scale (nominal, ordinal, interval, ratio), limited use of score distribution analysis, and inconsistent application of assessment standards contribute to discrepancies in grading outcomes. These inconsistencies often impact students’ perceptions of fairness and may influence learning motivation. Furthermore, the study highlights structural challenges such as lack of professional training, minimal feedback mechanisms, and limited technological integration in score processing. This research underscores the need for systematic professional development and standardized assessment frameworks to promote fairness, validity, and accountability in educational evaluation. The study also suggests integrating statistical tools and digital assessment platforms as strategies to enhance objectivity and transparency